An An Analysis of the Language Styles Used in Conversation between Craft Traders and Foreigners in Sukawati Market - Ketut Mitari Dewi (Jurnal Pendidikan Bahasa Inggris undiksha, 2022)
People will never use the same language to communicate because they have their own style. The way they choose the words or language style can be influenced by the setting of the conversation. Therefore, This study aims to analyze the style of language used by handicraft traders and foreign tourists in their conversation, the language style most often used, and the language function used by handicraft traders at the Sukawati market. This research was descriptive qualitative research. The subjects were two craft traders and twenty foreigners. Methods of collecting data by interview and observation. The research instrument was the researcher, observation sheet, interview, and voice recorder. The data analysis technique is descriptive qualitative analysis. The results of this study showed that the language styles used were the colloquial, casual, and consultative styles. From those styles, the consultative style was dominantly used by craft traders and foreigners. Moreover, the function of the language style used in the conversation was to persuade the foreigners to buy their merchandise, to make the speaker’s ideas clearer, to get foreigners’ attention, to create mood, and increase foreigners’ tastes or feeling.